THE ROLE OF NATIONAL IDENTITY AND CULTURAL DISCOURSE IN THE FORMATION OF AMERICAN LITERATURE (KELAJAK SARI YANGI O’ZBEKISTON: ILM-FAN, TEXNOLOGIYA VA TA’LIM, 2026)
This article examines the formation of American national literature and its connection with national identity. Based on Richard Gray’s historical analysis, the study explores how economic growth, territorial expansion, and social conflicts influenced literary discourse between 1800 and 1865. The research highlights the roles of slavery, the "Trail of Tears," and the "Second Great Awakening" in shaping the moral and ethical foundations of American writing. The findings suggest that literature served as a primary tool for constructing a cohesive national identity amidst deep social divisions. This article explores the formation of American national literature in close relation to the development of national identity and cultural discourse during the first half of the nineteenth century. Drawing on Richard Gray’s historical perspective, the study analyzes how rapid economic expansion, westward